Primary analysis and prioritization of risks of biowaiver procedure - Вісич, Світлана Юріївна; Русанова, Світлана Володимирівна; Андрюкова, Лариса Миколаївна; Доровський, Олександр Вікторович (ScienceRise: Pharmaceutical Science, 2016)
Aim: To conduct cause-effect analysis of identified risks, ranking and prioritization according to general risk assessment methodology to ensure proper execution of biowaiver procedure in compliance with necessary requirements for its reproduction. Methods: Was used method of cause-effect analysis with construction of Ishikawa diagram. Prioritization of risks was performed with help of expert evaluation. Results: Performed analysis allowed to identify the most influential risk factors, negative effect of which can cause significant consequences during conduction of bioequivalence studies of generic drug and reference drug based on biowaiver procedure. Conclusions: Identified and justified priorities among identified risks are carriers of primary causes of potential risk of problem arising in ensuring the quality of conduction of biowaiver procedure. Further studies should be linked to a more profound analysis and risk assessment with regard to their potential threat and probability and formulation of proposals for preventive actions to ensure compliance with established requirements of biowaiver procedure